1970
DOI: 10.1002/jlac.19707310116
|View full text |Cite
|
Sign up to set email alerts
|

Ring/Ketten‐Tautomerie bei 1.3.4‐Thiadiazolidin‐thionen‐(2) und Δ2‐1.3.4‐Thiadiazolinen

Abstract: Durch NMR-spektroskopische und chemische Untersuchungen wird nachgewiesen, da8 bisher als 1.3.4-Thiadiazolidin-thione-(2) 1 angesehene Verbindungen in Losung mit ihrer ,,Hydrazon-Form" 12 in einem Tautomerie-Gleichgewicht stehen, welches in alkalischem Milieu vollstandig zur ,,Hydrazonsalz-Form" 13 verschoben ist. Umgekehrt konnen bisher als linear aufgefal3te Verbindungen vom Typ 16 auch in Form tautomerer A2-I .3.4-Thiadiazoline 18 vorliegen. Ring1 Chain Tautomerisnz of 1,3,4-Thiadiazolidine-2-thiones and A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Insight as to whether pathway ( a ) or ( b ) (Scheme 6) would be preferred can be gained from consideration of the work of others on thiosemicarbazones, which have been found to be in a dynamic equilibrium with 1,3,4‐thiadiazolidines . The work of Uda and Kubota is particularly instructive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight as to whether pathway ( a ) or ( b ) (Scheme 6) would be preferred can be gained from consideration of the work of others on thiosemicarbazones, which have been found to be in a dynamic equilibrium with 1,3,4‐thiadiazolidines . The work of Uda and Kubota is particularly instructive.…”
Section: Resultsmentioning
confidence: 99%
“…Insight as to whether pathway (a) or (b) (Scheme 6) would be preferred can be gained from consideration of the work of others on thiosemicarbazones, which have been found to be in a dynamic equilibrium with 1,3,4-thiadiazolidines. [14][15][16][17][18][19][20] The work of Uda and Kubota 12 is particularly instructive. They observed that under neutral conditions the ring-chain equilibrium between acetone thiosemicarbazone and the corresponding 2-amino-1,3,4-thiadiazoline lies essentially completely on the side of the acyclic species.…”
Section: Formation Of a Cation At C5mentioning
confidence: 99%
“…They have recently gained attention as fungicides, 1 herbicides 2,3 and anticancer agents. [4][5][6] Figure 1 Structure of thiadiazolidine-2-thiones 3-Alkyl-and 3-aryl-1,3,4-thiadiazolidine-2-thiones can be prepared by reacting an aldehyde or ketone with Nalkyldithiocarbazic acid, [7][8][9][10][11][12][13] or by reacting carbon disulfide with hydrazones. 7,8,14,15 3,4-Dialkyl derivatives are synthesized by the reaction of 1,2-dialkylhydrazines with aldehydes and carbon disulfide.…”
mentioning
confidence: 99%
“…The open-chain forms (7) and the cyclic forms ( 12) may be differentiated on the basis of their n.m.r. spectra.…”
mentioning
confidence: 99%
“…Hz, 5'-H),6.92 (s, 5-H),7.07 (dd, J 8.5, 2.0 Hz, 6'-H),70.3d ((2-9, 108.1 (d), 109.1 (d), 109.9 (d), 110.7 (d), 120.8 (d), 2-Acetylamino-4,5-dimethoxybenzaldehyde Ethoxy(thi0-carbony1)hydrazone (6a).-(a) A mixture of compound (5a) (3.13 g, 10 mmol), 40% aqueous ethanol (140 cm3), and Na2S204 (5 1 g, 30 mmol) was stirred at 65-70 "C. After * Unprimed locants refer to the thiadiazoline ring, while primed locants refer to the 5-aryl group. t Unprimed locants refer to the thiadiazoline ring, primed Iocants to the 2-aryl group, and doubly primed locants to the 5-aryl group.…”
mentioning
confidence: 99%